Control system and measurements of coil actuators parameters for magnetomotive micropump concept - M. Szulborski; Ł. Kolimas; K. Bieńkowski; S. Łapczyński; Ł. Kozarek; K. Birek (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2020)
This paper presents an approach to the construction and measurements of electrodynamic and reluctance actuators. Executive elements were used as drives in a novel concept of a magnetomotive micropump. The paper discusses various aspects concerning the designation of parameters, control system, the explanation of physical phenomena, and the optimization of the basic elements for coil units. The conducted work describes the measurement system and the analysis of the derived values. The actuators were compared and the pros/cons of building the conceptual device were highlighted. The best solution to be used in the upcoming work concerning the construction of a magnetomotive micropump was chosen based on measurements, engineering aspects, layout control, and key parameters such as the piston velocity, energy stored in capacitors, and efficiencies.